The Revenue Administration-Gap Analysis Program : Model and Methodology for Value-Added Tax Gap Estimation - Hutton, Eric (Technical Notes and Manuals; Technical Notes and Manuals ;, 2017)
The IMF Fiscal Affairs Department's Revenue Administration Gap Analysis Program (RA-GAP) assists revenue administrations from IMF member countries in monitoring taxpayer compliance through tax gap analysis. The RA-GAP methodology for estimating the VAT gap presented in this Technical Note has some distinct advantages over commonly used methodologies. By using a value-added approach to estimating potential VAT revenues, as compared to the more traditional final consumption approach used by most countries undertaking VAT gap estimation, the RA-GAP methodology can provide VAT compliance gap estimates on a sector-by-sector basis, which assists revenue administrations to better target compliance efforts to close the gap. In addition, the RA-GAP methodology uses a unique measurement for actual VAT revenues, which isolates changes in revenue performance that might be due to cash management (e.g., delays in refunds) from those due to actual changes in taxpayer compliance.